Brand experience clustering and depiction of brand satisfaction, brand loyalty and emotional confidence - Wajid H. Rizvi; Salman Bashir Memon; Abdul Samad Dahri (Foundations of Management, 2020)
Brand experience (BE) is essential to depict long-term consumer brand relationships; this study investigates the influence of brand experience on emotional confidence (EC) and subsequent impact of brand satisfaction (BS) and brand loyalty (BL) in the context of car buying. Structural equation modeling was used to affirm the hypothesized relationships. This study further explores dimensions of brand experience: sensory, affective, intellectual and behavioral concerning EC, BS, and BL. Hierarchical cluster analysis was performed to depict the relationship as a consequence, and four clusters were identified. The results of the structural model suggest that there is a positive and statistically significant influence of BE on EC, there is a positive and statistically significant influence of EC on BS, and there is a positive and statistically significant influence of BS on BL. When the direct path from EC to BL was added to the model, it increased the variance explained in BL and coefficient of EC was higher than the coefficient of BS suggesting that EC is an important construct within the formwork. The results of hierarchical cluster analysis identified four clusters; the relationship among EC, BS and BL showed interesting patterns; there were higher correspondents between EC and BL than between BS and BL; the pattern was consistent with the results of the structural model. The data was collected from car showrooms across Karachi city; the respondents were users of the brand.
Keywords: M31; 650; brand experience; brand satisfaction; brand loyalty and emotional confidence